Living with Others. Living like Others. An ethical basis for intercultural education - Martino, Paola (Studi sulla Formazione/Open Journal of Education, 2017)
The Other, both guest and stranger, is what undermines the granitic concept of our reassuring identity, questions it, upsets its order and infects it by putting it on its own edge.  Exactly like the encounter with the stranger, education open up the possibility for us to be or not to be an Other, it is the process by which we recognise ourselves as identity stateless individuals.  Through the phenomenological analysis of Max Scheler, who, in contrast to every theoreticism of a solitary ego, sets the origin of the Other’s existence in the interpersonal sphere of the we (egoità-tuità), leading to an ethical re-foundation capable of exalting the emotional dimension in the definition of value (emotional apriorism), an attempt will be made to identify a possible ethical basis for intercultural education.